2003
DOI: 10.1108/03074800310504366
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of the effectiveness of Web‐based distance education

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 3 publications
(3 reference statements)
3
18
0
2
Order By: Relevance
“…The result of this study showed that the integrated approach took precedence over synchronous and asynchronous approaches. The result of this study is in line with the findings of earlier studies (e.g., Gregory, 2003;Ligorio, 2001). The findings illustrated that learners often preferred integrated approach due to the fact that this approach can foster language-learning process through developing language learners' potentialities and competencies.…”
Section: Resultssupporting
confidence: 82%
“…The result of this study showed that the integrated approach took precedence over synchronous and asynchronous approaches. The result of this study is in line with the findings of earlier studies (e.g., Gregory, 2003;Ligorio, 2001). The findings illustrated that learners often preferred integrated approach due to the fact that this approach can foster language-learning process through developing language learners' potentialities and competencies.…”
Section: Resultssupporting
confidence: 82%
“…Research carried out by Gregory (2003) reinforces the importance of synchronous interaction with peers and tutors for students studying Library and Information Science programs. In comparing communication methods across face-to-face and online study environments (separately), she highlights students' feelings of isolation with respect to tutors and peers in complete asynchronous communication methods for online learning courses.…”
Section: Literature Reviewmentioning
confidence: 75%
“…Faculty's potential and actual impacts on students' success or lack of success are discussed extensively in, e.g., McWilliam et al [2002], Gregory [2003], and UCLA Graduate Division [2000]. On the importance of faculty's share of success, according to Marsh et al [2002, p. 319, citing Monk, 1992, BOne of the recurring and most compelling findings within the corpus of production function research is the demonstration that how much a student learns depends on the identity of the instructor to which that student is assigned.^(p. 320).…”
Section: Faculty's Share Of Successmentioning
confidence: 99%